(untitled) (Revista Argentina de Cirugía, 2021)
The recommendations and guidelines generated by Asociación Argentina de Cirugía during the COVID-19 pandemic should be implemented according to the following: The leading surgeon of the team is responsible for the decisions made concerning the surgical procedure, according to the regulations issued by the Crisis Committee of each institution, and to the phase or stage of the pandemic (classification of the Spanish Association of Surgeons) in the corresponding geographical area and ad referendum of the Regional Health Authority.